2014
DOI: 10.2174/1876823701406010038
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness and Physical Activity in Swedish Women before and one Year after Roux-en-Y Gastric Bypass Surgery

Abstract: Abstract:Introduction: Obesity is associated with a sedentary life style, which has a negative impact on physical fitness.Aim: To investigate physical fitness, physical activity level and time spent sitting in Swedish women before and one year after laparoscopic Roux-en-Y Gastric Bypass surgery (LRYGB).Method: Thirty-seven women (age: 41.2±9.6 years and Body Mass Index (BMI): 42±6.5 kg/m 2 ) were tested before and one year after LRYGB. (BMI: 30.5±5.8 kg/m 2 ). Physical fitness was assessed using the six minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The majority of studies were performed in the USA , with five conducted in the Netherlands and four in Brazil . The types of bariatric surgery received by participants varied between studies, but the two main surgery types were Roux‐en‐y gastric bypass (29 studies) and gastric banding (8 studies) . Fourteen studies reported a physical activity outcome , 30 reported a physical function outcome and six reported both physical function and physical activity data .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies were performed in the USA , with five conducted in the Netherlands and four in Brazil . The types of bariatric surgery received by participants varied between studies, but the two main surgery types were Roux‐en‐y gastric bypass (29 studies) and gastric banding (8 studies) . Fourteen studies reported a physical activity outcome , 30 reported a physical function outcome and six reported both physical function and physical activity data .…”
Section: Resultsmentioning
confidence: 99%
“…All studies assessing cardiovascular endurance outcomes reported improvements post‐surgery (Table ). These included 20 tests of walking performance (treadmill exercise test, fastest possible walking speed, walking speed, walking minutes per week, 6‐min‐walk test [6MWT], 4‐m‐walk time, walking energy expenditure) and two of cycle ergometer endurance . Meta‐analysis based on 11 studies showed an increase in walking performance at 3–6 months (SMD: 0.82; 95% CI: 0.57 to 1.06), with a heterogeneity score of I 2 = 43% (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty studies with a total of 1779 patients were identified as suitable for meta‐analysis of the effect of bariatric surgery on physical function. Objective measurement of physical function was undertaken in 21 of the 30 studies, and nine studies employed self‐reporting by patients.…”
Section: Resultsmentioning
confidence: 99%
“… Table S1 Characteristics of studies included in the meta‐analysis of physical function before and after bariatric surgery Table S2 Characteristics of studies excluded from the meta‐analysis of physical function before and after bariatric surgery Table S3 Assessment of risk of bias in studies included in the meta‐analysis of physical function before and after bariatric surgery …”
mentioning
confidence: 99%